2011
DOI: 10.1016/j.cppeds.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Origins of Adult Disease

Abstract: Dr. David Barker first popularized the concept of fetal origins of adult disease (FOAD). Since its inception, FOAD has received considerable attention. The FOAD hypothesis holds that events during early development have a profound impact on one’s risk for development of future adult disease. Low birth weight, a surrogate marker of poor fetal growth and nutrition, is linked to coronary artery disease, hypertension, obesity, and insulin resistance. Clues originally arose from large 20th century, European birth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
364
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(398 citation statements)
references
References 146 publications
(186 reference statements)
8
364
0
9
Order By: Relevance
“…These findings have been observed in populations that have experienced significant famines but occur in many situations in which malnutrition in the form of lack of food or access to poorly nutritious but highly caloric food exists. 316 Numerous studies support the fetal origins hypothesis by demonstrating an association among low birth weight, placental insufficiency, and cardiovascular and other chronic diseases. Adult-onset systemic hypertension has been associated with birth weight.…”
Section: Effect Of Prenatal/early Childhood Deprivation On Cvd Incidementioning
confidence: 97%
See 1 more Smart Citation
“…These findings have been observed in populations that have experienced significant famines but occur in many situations in which malnutrition in the form of lack of food or access to poorly nutritious but highly caloric food exists. 316 Numerous studies support the fetal origins hypothesis by demonstrating an association among low birth weight, placental insufficiency, and cardiovascular and other chronic diseases. Adult-onset systemic hypertension has been associated with birth weight.…”
Section: Effect Of Prenatal/early Childhood Deprivation On Cvd Incidementioning
confidence: 97%
“…Intrauterine growth retardation is associated with a reduced number and function of pancreatic β cells, resulting in decreased insulin production. 316 This alteration leads to abnormal muscle, liver, and adipocyte insulin signaling and eventually to the development of insulin resistance.…”
Section: Effect Of Prenatal/early Childhood Deprivation On Cvd Incidementioning
confidence: 99%
“…If, during that individual' s adult life, nutrients become more plentiful, this predisposition increases the risk of obesity and metabolic syndrome over time. 5 This hypothesis differs from the thrifty genotype hypothesis, another proposed explanation for the increasing levels of obesity in Western society. The thrifty genotype hypothesis holds that populations that evolved over generations to survive in harsh environments cannot adapt to the modern environment because the change was too dramatic to allow for evolutionary adaptation over a short time frame.…”
Section: Epigenetic Hypothesesmentioning
confidence: 46%
“…Intrauterine environment and early postnatal life are now generally accepted as important factors that may lead to increased risk for disease in adulthood (Hofman et al 2004). In particular, low birth weight, a marker of poor fetal growth, is linked to vascular disease, hypertension, obesity, and insulin resistance (Calkins and Devaskar 2011). Although several studies have reported an association between low birth weight and poor adult health outcomes, it remains unclear whether this association exists for children with poor fetal growth born small for gestational age as well as premature babies whose weight is appropriate for gestational age.…”
Section: The Impact Of Fetal Environment and Prematurity On Adult Heamentioning
confidence: 87%